Synthesis of an eight-membered 2,2,4,6,6,8-hexaphenyl-1,3,5,7,2,6,4,8-tetraoxadisiladiborocane and its reaction with 4,4-azo-pyridine leading to ring contraction to give a dimer and hydrogen bonded macrocyclic siloxane-azo-pyridine - Bull, Okpara Sergeant; Don-Lawson, Chioma; Ahuchaogu, Ahamefula Anslem (European Journal of Chemistry, 2025)
We hereby report the syntheses and characterization of a new dimer of azopyridine connected through the six-membered B-N dative-bonded-adduct Ph8B4Si2O6·L (4) and a hydrogen-bond-induced macrocyclic product 4(Ph2Si(OH)2)·3(C10H8N4) (5). The products were obtained after an eight-membered 2,2,4,6,6,8-hexaphenyl-1,3,5,7,2,6,4,8-tetraoxa disiladiborocane (Ph6B2Si2O4) (3), which is abundant in the literature, was successfully synthesized and characterized by standard analytical and spectroscopic methods such as single-crystal XRD, melting point, nuclear magnetic resonance and Fourier transform infrared spectroscopy. Subsequently, compound 3 and 4,4-azopyridine (L) were reacted in a mixture of diethyl ether and petroleum ether solvents at reflux. This reaction caused a contraction of the eight-membered compound 3 to give two products - a dimer compound 4 (Ph8B4Si2O6·L), and a macrocyclic product 4(Ph2Si(OH)2)·3(C10H8N4) (5). These two products have been characterized by single-crystal XRD, nuclear magnetic resonance, Fourier transform infrared spectroscopy, and melting point. Single crystal X-ray diffraction studies reveal that the dimer compound 4 compound crystalized in the monoclinic crystal system with a centrosymmetric space group of P21/c, a = 11.0879(4) Å, b = 14.3707(4) Å, c = 16.2697(5) Å, β = 98.759(3)°, V = 2562.20(13) Å3, Z = 2. On the other hand, the macrocyclic product 4(Ph2Si(OH)2)·3(C10H8N4) (5) is orange blocky needles that crystallized in the triclinic crystal system with a centrosymmetric space group of P-1, a = 12.2352(3) Å, b = 15.3274(6) Å, c = 20.0271(6) Å, α = 89.879(3)°, β = 89.988(2)° γ = 78.298(3)°, V = 3677.7(2) Å3, Z = 2. Furthermore, compounds 4 and 5 exhibit various noncovalent interactions in crystal packing, such as intermolecular and intramolecular π-π as well as hydrogen bonding. This study demonstrates the potential for making novel materials via the combination of cyclodiboradisiloxane (a Lewis acid) and nitrogen-containing ligand (a Lewis base).